Memes as a Factor of Manipulations: Transformation of Image Through Mass Culture - Наталія Войтович; Іван Магуряк (Український інформаційний простір)
The article studies the phenomenon of political me es as a powerful tool for inﬂuencing public opinion and politicians’ ratings. The authors analyse the role of memes in grounding images of political leaders, in particular, using examples from the Ukrainian and American political contexts. It views how memes can inﬂuence the perception of politicians, changing their perception by society. In Ukraine, Petro Poroshenko became an object of numerous memes, which were mostly aimed at criticising his political activities and inefﬁciency, which, in turn, reduced his rating among voters. At the same time, memes around Yulia Tymoshenko became a mechanism for popularising her image among young people, reinforcing the image of a leader capable of change.